1998
DOI: 10.1002/j.2164-4683.1998.tb00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Behavioral Indicators of Self‐Esteem in the Classroom

Abstract: This study aimed to develop and validate an instrument to be used by teachers to measure the frequency of behaviors indicative of self‐esteem and then to evaluate the instruments' reliability and concurrent validity. The Behavioral Indicators of Self‐Esteem (BIOS) Scale proved to be a reliable and valid measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…This supported our expectation of an association between negative perceptions of self-esteem and passivity in school. The current finding is in accordance with previous research on selfesteem and participation in the classroom that have suggested that students with low self-esteem are passive in the classroom (Burnett 1998). Students with low self-esteem may cause this by adjusting their performance to a lower level of social interaction or avoiding social situations because of fear of failure, which again may threaten their self-esteem.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This supported our expectation of an association between negative perceptions of self-esteem and passivity in school. The current finding is in accordance with previous research on selfesteem and participation in the classroom that have suggested that students with low self-esteem are passive in the classroom (Burnett 1998). Students with low self-esteem may cause this by adjusting their performance to a lower level of social interaction or avoiding social situations because of fear of failure, which again may threaten their self-esteem.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, self-esteem has been correlated with the level of classroom participation (Burnett 1998). Research on self-esteem and participation in school has found that several behavioural differences among students with varying levels of self-esteem exist (Burnett 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…reported a reliability coefficient of 0.85 for MALS, but lower correlations with related measures (which might themselves be unstable). 2 Behavioural Indicators of Self-esteem (BIOS) (Burnett, 1998) -a measure of observable changes in self-esteem completed for the Primary 7 and Primary 3 participants by their respective class teachers -pre-and post-intervention. This required teachers to respond to 13 statements about each child on a fivepoint multiple-choice scale from Never to Always.…”
Section: Instrumentationmentioning
confidence: 99%